2001
DOI: 10.1097/00000539-200109000-00039
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Toxicity and Resuscitation in Bupivacaine-, Levobupivacaine-, or Ropivacaine-Infused Rats

Abstract: We compared the systemic toxicity of bupivacaine, levobupivacaine, and ropivacaine in anesthetized rats. We also compared the ability to resuscitate rats after lethal doses of these local anesthetics. Bupivacaine, levobupivacaine, or ropivacaine was infused at a rate of 2 mg. kg(-1). min(-1) while electrocardiogram, electroencephalogram, and arterial pressure were continuously monitored. When asystole was recorded, drug infusion was stopped and a resuscitation sequence was begun. Epinephrine 0.01 mg/kg was adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
88
2
9

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(100 citation statements)
references
References 24 publications
1
88
2
9
Order By: Relevance
“…Experimental research has shown lower incidence of failed cardiopulmonary resuscitation after ropivacaine as compared to bupivacaine. In rats, Ohmura et al 30 have emphasized that ropivacaine-induced cardiac arrest seems to respond better to treatment than that induced by bupivacaine or levobupivacaine, which is in line with what is seen in humans 1,7,8,11 . Groban et al 31 have reported lower incidence of epinephrine-induced ventricular fibrillation in dogs intoxicated with ropivacaine as compared to bupivacaine.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Experimental research has shown lower incidence of failed cardiopulmonary resuscitation after ropivacaine as compared to bupivacaine. In rats, Ohmura et al 30 have emphasized that ropivacaine-induced cardiac arrest seems to respond better to treatment than that induced by bupivacaine or levobupivacaine, which is in line with what is seen in humans 1,7,8,11 . Groban et al 31 have reported lower incidence of epinephrine-induced ventricular fibrillation in dogs intoxicated with ropivacaine as compared to bupivacaine.…”
Section: Discussionmentioning
confidence: 56%
“…A pesquisa experimental revela incidência menor de reanimação cardiopulmonar mal sucedida após ropivacaína, quando comparada à bupivacaína. Em ratos, Ohmura e col. 30 enfatizaram que a parada cardíaca induzida pela ropivacaína parece ser mais susceptível ao tratamento que aquela provocada pela bupivacaína ou levobupivacaína, o que está de acordo com o que se encontra em seres humanos 1,7,8,11 . Groban e col. 31 relataram menor incidência de fibrilação ventricular induzida pela epinefrina em cães intoxicados com ropivacaína, quando se comparou com bupivacaína.…”
Section: Discussionunclassified
“…18,19 The incidence of systemic toxicity from local anesthetics appears to be decreasing with the use of safer local anesthetics 20,21 and the widespread introduction of procedural safety. 20 Since dextromethorphan and dextrorphan are better tolerated systemically than bupivacaine in this animal model, these drugs should be investigated further as possible useful local anesthetics in the clinical setting.…”
Section: áMinmentioning
confidence: 99%
“…7,9,11,12,15 Ropivacaine, which has less CV toxicity than bupivacaine, was subsequently introduced into clinical practice. 19,22 However, ropivacaine is at least 40% less potent than bupivacaine. 23 We did not compare the toxicity of dextromethorphan and dextrorphan with that of ropivacaine, although this comparison could be worthwhile investigating in the future.…”
Section: áMinmentioning
confidence: 99%
“…BUPI is a long-acting anesthetic, which can be used in long surgeries without the need for anesthetic complementation. However, it exhibits a certain degree of cardiotoxicity, caused by the dextrorotatory enantiomer in the racemic mixture (S50-R50), which encouraged researchers to develop an anesthetic with a lower toxic potential 4,5 .…”
Section: Introductionmentioning
confidence: 99%